2008
DOI: 10.1086/523762
|View full text |Cite
|
Sign up to set email alerts
|

Direct In Vivo Assessment of Microcirculatory Dysfunction in Severe Falciparum Malaria

Abstract: Patients with severe falciparum malaria show extensive microvascular obstruction that is proportional to the severity of the disease. This finding underscores the prominent role that microvascular obstruction plays in the pathophysiology of severe malaria and illustrates the fundamental difference between the microvascular pathophysiology of malaria and that of bacterial sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
196
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(212 citation statements)
references
References 22 publications
4
196
2
3
Order By: Relevance
“…21 Such high specificity in the present study might be found with a very sensitive test that is able to detect malaria antigens in the presence of very low parasites that are not detected by microscopy. 24 Such variations within the same test could be explained by the persistence of HRP2 in patients who had been treated 28 days before in case of P. falciparum 12 and the sequestration [25][26][27] Sequestration may reduce the number of circulating parasites to below the microscope threshold detection level. 23 RDT-based diagnosis is vital to make treatment decisions at all health facility levels in general and the peripheral areas in particular, where there is no microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…21 Such high specificity in the present study might be found with a very sensitive test that is able to detect malaria antigens in the presence of very low parasites that are not detected by microscopy. 24 Such variations within the same test could be explained by the persistence of HRP2 in patients who had been treated 28 days before in case of P. falciparum 12 and the sequestration [25][26][27] Sequestration may reduce the number of circulating parasites to below the microscope threshold detection level. 23 RDT-based diagnosis is vital to make treatment decisions at all health facility levels in general and the peripheral areas in particular, where there is no microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…This swelling is partly attributed to venous congestion by the sequestered IRBC mass causing increased cerebral blood volume. 25 Brain herniation is not seen, nor is there evidence of toxigenic or vasogenic edema. 21 This would be in keeping with a lack of detection of albumin or IgG leakage into the CSF of adult patients with CM, in contrast to the significant leakage seen during bacterial meningitis.…”
Section: Clinical Evidence Of Barrier Dysfunction In Severe Malariamentioning
confidence: 98%
“…[50][51][52][53] More recently, obstruction of the microcirculation that is reversed after anti-malarial therapy has also been documented in vivo in acutely infected patients. 25 Sequestration results from the adhesion, or cytoadherence, of IRBC to vascular endothelial cells, and the process is mediated by the variant parasite ligand Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) expressed on the surface of IRBC, and endothelial receptors, of which a number have been implicated. 54,55 Cytoadherence occurs to any significant extent only with P. falciparum that infects human Figure 2.…”
Section: Cytoadherencementioning
confidence: 99%
“…Noninvasive imaging of retinal and rectal vessels in patients with CM clearly demonstrates hypoperfusion and occlusion of the microcirculation, [15][16][17][18][19][20][21] which is reflected by a clear association with a poor clinical outcome. 16,[21][22][23] Murine models of CM have important similarities to CM in humans 2,24 including increased intracranial pressure and a significant decrease in cerebral blood flow, which progressively deteriorates as the clinical condition becomes aggravated. 25 The decrease in cerebral blood flow leads to an altered metabolic profile in the cerebral tissue, which suggests cerebral ischemia.…”
mentioning
confidence: 99%